Concrete in-filled steel tubes under combined axial load and lateral cyclic load - state - of - the - art review - Gajalakshmi, P.; Helena, H. Jane (Journal of Structural Engineering, 2025)
The use of Plain Cement Concrete (PCC) filled steel columns for construction of high rise buildings, bridges etc., has become widespread in recent times. Concrete in-filled steel columns provide high strength, high ductility and full usage of both concrete and steel. The steel tube acts not only as longitudinal reinforcement to resist the loads but also as effective lateral ties to confine the concrete in-fill and hence both the strength and the ductility of the concrete are enhanced. On the other hand, the risk of local buckling of the steel tube is significantly reduced because of the rigid concrete in-fill. This paper presents the state - of - the - art of steel-concrete composite columns subjected to cyclic lateral load in addition to axial load. A review of experimental and analytical work carried out on the concrete in-filled steel composite columns subjected to axial load and cyclic lateral load has been presented. This paper also focuses on the influence of various parameters such as shape of the section, type of loading, methods of accounting the effects of bond strength, effect of additional confinement, width-thickness ratio, number of loading cycles, length of filled concrete inside the steel tube, and concrete compressive strength on the behaviour of concrete in-filled steel columns.